A critical analysis of quality assurance of occupational learning in South Africa. - Traut, Nadia (My University, 2015)
The introduction of the National Qualifications Framework (NQF) brought with it decentralised learning and assessment practices and associated quality assurance systems that have been extensively critiqued over the past 19 years. This research utilised the case study approach to examine quality assurance of occupational education in South Africa in respect of three quality assurance cases of occupational learning. The analysis was conducting using a Quality Assurance Analytic Tool developed for this study that included analytic categories of ‘Purpose’; ‘Map of Qualifications’; ‘Bureaucracy’; and ‘Agreements’. Despite each case providing unique data in terms of the model implemented, a recurring pattern emerged: while quality assurance is necessary to provide accountability to the stakeholders and is ultimately obligated to support the objectives of the NQF and ensure consistency across provision sites, definitions of quality were lacking and this creates a barrier to evaluation. This research agrees with literature which argues that quality assurance is justified as the custodian of quality in order to satisfy public accountability. However, quality must be defined and shared, so that all role players are aware of the goals and measurements. The study also argues that quality assurance should ensure consistency of output of education and training and as such, standardised curriculum, centralised assessment and associated quality assurance mechanisms should be put in place. Finally, recommendations are made for the improvement of the Quality Assurance Analytic Tool that was able to effectively evaluate what was working broadly in respect of the categories investigated and was able to conclude that effective evaluation is largely dependent on the articulation of clear and specific objectives for quality assurance and definitions of quality, but was not able to evaluate achievement of quality assurance in great detail.